PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PT. PELABUHAN INDONESIA II (PERSERO) CABANG PALEMBANG - nina fitriana; Agustina Marzuki (Fakultas Ekonomi Universitas Tridinanti Palembang, 2012)
ABSTRACTFormulation of the problem in this study is how the influence of Labor Discipline Ã‚Â and Supervision to Performance of PT. Port of Indonesia II (Persero) Branch Palembang. This case study aims to determine the effect of Labor Discipline and Supervision Ã‚Â of Employee Performance PT. Port of Indonesia II (Persero) Branch Palembang. In this study used probability sampling with a sample of 42 respondents. While the design of this study is the influence of relationship between variables - variables using the survey method is to look at the influence of the independent variables consist of labor discipline (X1), supervision (X2) with the performance dependent variable (Y) PT. Port of Indonesia II (Persero)Branch Palembang. The results showed that the relationship between discipline and supervision work very closely with Employee Performance. The existence of significant influence of labor discipline and supervision of the employee's performance either partially orÃ‚Â simultaneously, Keywords: Labor Discipline, Supervision, Performance